Destruction in Bat Yam, Israel after missile attack (WP Company LLC d/b/a The Washington Post, 2025)
Footage shows the aftermath of an Iranian missile strike in Bat Yam, Israel, on June 15. Crews sift through rubble in ongoing rescue efforts.